Narratives of possession: Reading for saga authorship - Kári Gíslason 1972- (2003)
Doktorsritgerð varin við The University of Queensland í Brisbane, Ástralíu. The aim of this thesis is to show how character analysis can be used to approach conceptions of saga authorship in medieval Iceland. The idea of possession is a metaphor that is adopted early in the thesis, and is used to describe Icelandic sagas as works in which traditional material is subtly interpreted by medieval authors. For example, we can say that if authors claim greater possession of the sagas, they interpret, and not merely record, the sagas' historical information. On the other hand, tradition holds onto its possession of the narrative whenever it is not possible for an author to develop his own creative and historical interests. The metaphor of possession also underpins the character analysis in the thesis, which is based on the idea that saga authors used characters as a vehicle by which to possess saga narratives and so develop their own historical interests. The idea of possession signals the kinds of problems of authorship study which are addressed here, in particular, the question of the authors' sense of saga writing as an act either of preservation or of creation. While, in that sense, the thesis represents an additional voice in a long-standing debate about the saga writers' relation to their source materials, I argue against a clear-cut distinction between creative and non-creative authors, and focus instead on the wide variation in authorial control over saga materials. This variation suggests that saga authorship is a multi-functional activity, or one which co-exists with tradition. Further, by emphasising characterisation as a method, I am adding to the weight of scholarship that seeks to understand the sagas in terms of their literary effects.